2003
DOI: 10.1038/sj.bjp.0705542
|View full text |Cite
|
Sign up to set email alerts
|

Thymol, a constituent of thyme essential oil, is a positive allosteric modulator of human GABAA receptors and a homo‐oligomeric GABA receptor from Drosophila melanogaster

Abstract: 1 The GABA-modulating and GABA-mimetic activities of the monoterpenoid thymol were explored on human GABA A and Drosophila melanogaster homomeric RDL ac GABA receptors expressed in Xenopus laevis oocytes, voltage-clamped at À60 mV. The site of action of thymol was also investigated. 2 Thymol, 1 -100 mM, resulted in a dose-dependent potentiation of the EC 20 GABA response in oocytes injected with either a1b3g2s GABA A subunit cDNAs or the RDL ac subunit RNA. At 100 mM thymol, current amplitudes in response to G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
273
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 455 publications
(284 citation statements)
references
References 37 publications
4
273
0
7
Order By: Relevance
“…and J.A., unpublished results). Oocyte collection, injection and electrophysiological recordings were carried out as described 35,36 . Two electrode voltage-clamp experiments were performed 1-5 d post-injection.…”
Section: Electrophysiological Recordingmentioning
confidence: 99%
“…and J.A., unpublished results). Oocyte collection, injection and electrophysiological recordings were carried out as described 35,36 . Two electrode voltage-clamp experiments were performed 1-5 d post-injection.…”
Section: Electrophysiological Recordingmentioning
confidence: 99%
“…Various studies have indicated that monoterpenoids may have several mechanisms of action. Mechanisms that have been reported include: inhibition of acetylcholinesterase (5,6), binding at the GABA receptor (7)(8)(9)(10)(11), binding at the nicotinic acetylcholine receptor (12), the octopamine receptor (13,14), and the tyramine receptor (15). Previous studies have also described quantitative structure-activity relationships (QSARs) to describe the toxicity of monoterpenoids and their interaction at the GABA receptor (11).…”
mentioning
confidence: 99%
“…Their constituents range from terpene hydrocarbons, simple and terpene alcohols, aldehydes, ketones, phenols, lactones, coumarins, to sulfur compounds. Yet the phytochemicals citronellol, linalool, and thymol (for having recognized antimicrobial activities) all stand out (Pereira et al, 2003;Priestley et al, 2003;Botelho et al, 2007).…”
Section: Introductionmentioning
confidence: 99%